Diversion Provisions in Criminal Law: A Normative Review of Diversion in Cases of Children in Conflict with the Law - Acmad Royani; Syamsul Arifin; Fajar Seto Nugroho; Dewi Indah Suryani (Jurnal Independent, 2025)
Children are individuals who are in the development stage and have special vulnerabilities, especially when dealing with the law. The state has a constitutional obligation to provide legal protection for children in conflict with the law, as regulated in the 1945 Constitution and a number of national laws and regulations, and reinforced by international conventions such as the CRC. This study aims to examine the regulation of the human rights of children involved in the criminal law process and to examine the implementation of the diversion mechanism at the investigation stage as a form of restorative justice in the juvenile criminal justice system. The method used is normative juridical with a statute approach to primary legal materials such as the 1945 Constitution, the SPPA Law, and its implementing regulations. The results of the study show that although the regulations have provided a strong legal basis to guarantee the protection and recovery of children, the implementation of diversion still faces structural and cultural obstacles, such as limited understanding of the apparatus and minimal support for facilities. Therefore, it is necessary to strengthen institutional capacity, increase cooperation between institutions, and update the legal approach that is oriented towards the best interests of children.